GAMBARAN PENGETAHUAN, SIKAP, DAN PERILAKU PEMAKAIAN KELAMBU BERINSEKTISIDA TAHAN LAMA (KBTL) (STUDI DI WILAYAH KERJA PUSKESMAS KALIGESING KABUPATEN PURWOREJO) - Dina Dwi Septiyani; M. Arie Wuryanto; Ari Udiyono (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Background. In 2017, the event who named Pekan Kelambu Anti Nyamuk Massal di daerah Fokus (PKMF) was implemented to achieve the target of malaria elimination in 2030. A total of 8 villages in Kaligesing Health Center, Purworejo District received the highest number of 11,302 Long Lasting Insecticidal Net‟s (LLIN‟S) with a total of 5,531 households. From 2015-2016, Kaligesing Health Center had received LLIN‟s for 218 malaria patients but had not changed the status of endemicity with API of 2015-2017 is 6,16, 4,75, 1,24. The purpose of this study was to describe knowledge, attitude and the usage behavior of Long Lasting Insecticidal Net‟s (LLIN‟S).Methods. Descriptive research with cross sectional approach. A total of 100 respondents of 5.531 households who received bed nets that met the criteria to be the subject of research. The sampling method used was simple random sampling with a proportion formula for 8 villages. These villages were Jatirejo, Somongari, Donorejo, Tlogoguwo, Pandanrejo, Kaligono, Kaliharjo and Sudorogo.Results. There was 69% of respondents had good knowledge. The percentage of good and bad attitudes towards received LLIN’s programs was almost the same (1.3:1). 63% of respondents were disposed to set LLIN’s and 53% slept in LLIN’s every night. Conclusion. From this study it can be concluded that the level of good knowledge was more often found in respondents from college/academy graduates, as well as respondents who did not work, and respondents who had good knowledge and attitude to slept more in LLIN’s every night.